The role of tissue resident cells in neutrophil recruitment - Kim, Nancy D. (Trends Immunol, 2015)
Neutrophils are first responders of the immune system, rapidly migrating into affected tissues in response to injury or infection. To effectively call in this first line of defense, strategically placed cells within the vasculature and tissue respond to noxious stimuli by sending out coordinated signals that recruit neutrophils. Regulation of organ-specific neutrophil entry occurs at two levels. First, the vasculature supplying the organ provides cues for neutrophil egress out of the bloodstream in a manner dependent upon its unique cellular composition and architectural features. Second, resident immune cells and stromal cells within the organ send coordinated signals that guide neutrophils to their final destination. Here, we review recent findings that highlight the importance of these tissue-specific responses in the regulation of neutrophil recruitment and the initiation and resolution of inflammation.